LESSONS FOR CONTEMPORARY YOUTH FROM THE WORKS OF ALEXANDER FEINBERG - Mamatova Dilnavo Sayqan qizi; Bazarov Ixtiyor (TADQIQOTLAR, 2026)
Abstract.  This  article  explores  the  essence  of  Aleksandr  Feinberg's  creative work and its significance in educating today's youth. It analyzes key themes reflected in the poet's works, such as humanity, patriotism, kindness, and the appreciation of life's beauty. Furthermore, the article discusses the impact of Feinberg’s legacy on the spiritual  development  of  the  younger  generation  and  the  profound  life  lessons  his poetry imparts.